Surgical complications of laparoendoscopic single‐site donor nephrectomy: a retrospective study. (27th July 2017) - LaMattina, John C.; Powell, Jessica M.; Costa, Nadiesda A.; Leeser, David B.; Niederhaus, Silke V.; Bromberg, Jonathan S.; Alvarez‐Casas, Josue; Phelan, Michael S.; Barth, Rolf N.
Summary: The single‐port approach has been associated with an unacceptably high rate of umbilical port hernias in large series of patients undergoing single‐port cholecystectomy and colectomy and with additional surgical risks thought secondary to technical and ergonomic limitations. A retrospective review of 378 consecutive laparoendoscopic single‐site(LESS) donor nephrectomies performed between 04/15/2009 and 04/09/2014 was conducted. Twelve patients (3%) developed an umbilical hernia. Eleven (92%) were female and eight (73%) of these patients had a prior pregnancy. Hernias were reported 13.5 ± 6.9 months after donation, and the mean size was 5.1 ± 3.7 cm. Seven additional cases (1.9%) required a return to the operating room for internal hernia (2), evisceration (1), bleeding (1), enterotomy (1), and wound infection (2). The original incision was utilized for reexploration. One patient required emergent conversion to an open procedure for bleeding during the initial donation. There were no mortalities. Recipient patient and graft survival were 99% and 99% at 1 year, respectively. Although reports associated with earlier experiences with single‐site procedures suggested an unacceptably high rate of hernias at the surgical site, this does not seem to be the case at our center. This technique is a reliable surgical technique for left donor nephrectomy at this institution.